Sensory-motor transformations for speech occur bilaterally - Cogan, Gregory B. (2014)
Historically, the study of speech processing has emphasized a strong link between auditory perceptual input and motor production output(1–4). A kind of ‘parity’ is essential, as both perception- and production-based representations must form a unified interface to facilitate access to higher order language processes such as syntax and semantics, believed to be computed in the dominant, typically left hemisphere(5,6). While various theories have been proposed to unite perception and production(2,7), the underlying neural mechanisms are unclear. Early models of speech and language processing proposed that perceptual processing occurred in the left posterior superior temporal gyrus (Wernicke’s area) and motor production processes occurred in the left inferior frontal gyrus (Broca’s area)(8,9). Sensory activity was proposed to link to production activity via connecting fiber tracts, forming the left lateralized speech sensory-motor system(10). While recent evidence indicates that speech perception occurs bilaterally(11–13), prevailing models maintain that the speech sensory-motor system is left lateralized(11,14–18) and facilitates the transformation from sensory-based auditory representations to motor-based production representations(11,15,16). Evidence for the lateralized computation of sensory-motor speech transformations is, however, indirect and primarily comes from lesion patients with speech repetition deficits (conduction aphasia) and studies using covert speech and hemodynamic functional imaging(16,19). Whether the speech sensory-motor system is lateralized like higher order language processes, or bilateral, like speech perception is controversial. Here, using direct neural recordings in subjects performing sensory-motor tasks involving overt speech production, we show that sensory-motor transformations occur bilaterally. We demonstrate that electrodes over bilateral inferior frontal, inferior parietal, superior temporal, premotor, and somatosensory cortices exhibit robust sensory-motor neural responses during both perception and production in an overt word repetition task. Using a non-word transformation task, we show that bilateral sensory-motor responses can perform transformations between speech perception- and production-based representations. These results establish a bilateral sublexical speech sensory-motor system.